Improved Treatment of Knee Meniscus Injuries and Reduced Need for Surgery with a Combination of Tisseel Fibrin Glue and Orthokine ACS: A 4-Year Follow-Up Archive Study - Strumper, Rudolf W.; Reinecke, Julio; Rechmeier , Johann W.; Schilling, Rene; Wehling, Peter (Research Highlights in Disease and Health Research Vol. 5, 2023)
Aim: The present study highlights a Retrospective analysis of clinical data of intra-articular fibrin glue fixation combined with ACS injections in clinical cases of routine outpatients presenting with knee pain and MRI- confirmed meniscal defects. Background: Knee injury is a significant risk factor for developing knee OA, Meniscus injuries are a common type of knee injury. It is now common practise to use biological therapies with potentially regenerative augmentation of tissue repair. Stem cells, platelet preparations, recombinant growth factors, and autologous conditioned serum (ACS) are among the techniques used, which are sometimes combined with other techniques such as matrices, surgery, and fibrin glue. ACS contains factors released by blood cells that have the potential to improve tissue repair or regeneration. Methods: An established intra-articular injection treatment method for osteoarthritis involving autologous conditioned serum (ACS) was routinely employed. ACS is prepared from patient’s blood subjected to extended coagulation at physiologic temperature. The serum supernatant is separated from cellular components by centrifugation. Results: 8 of 170 patients chose surgical treatment of the meniscal injury. 162 patients avoided surgery during the period analyzed. Mean WOMAC global score improved from 34.62 (SD ± 18.48) to 13.18 (SD ± 9.52) (p = 0.0015) at 4 years. Conclusion: The main advantages of this approach include: no surgical risk, no risk from general anesthesia, no irradiation, no thrombosis, no need for hospitalization, meniscus can be preserved, leaks of proteolytic enzymes from damaged meniscus cells are sealed, no immobilization and no muscle atrophy. If the technique fails, no obstacles stand in the way of surgery.